Інноваційний розвиток підприємств - Коваль, Л. А.; Koval, L. (ЦНТУ, 2018)
Методичні вказівки містять перелік питань до кожної теми, тести задачі до семінарських занять до вивчення предмету Інноваційний розвиток підприємств рекомендовану літературу. Methodical instructions contain a list of questions for each topic, tests of the task for seminars for studying the subject Innovative development of enterprises recommended literature.
Innovative development of enterprises
Keywords: інноваційний розвиток підприємств; семінар; рекомендована література; проблемні питання; тести; задачі; innovative development of enterprises; seminar; recommended books; problematic issues; tests; tasks